Integrating Classical with Emerging Concepts for Better Understanding of Salinity Stress Tolerance Mechanisms in Rice - Kaur, Navdeep; Pati, Pratap Kumar (Frontiers in Environmental Science, 2017)
Rice is an important cereal crop responsible for world’s food security. The sensitivity of rice plants towards a range of abiotic stresses is a prime challenge for its overall growth and productivity. Among these, salinity is a major stress which results in a significant loss of global rice yield annually. For finding straightforward and strict future solutions in order to assure the food security to growing world population, understanding of the various salt stress tolerance mechanisms in rice is of paramount importance. Plants combat the effects of salt stress through various mechanisms that operate at different levels. Diverse strategies have been adopted for understanding and unraveling the key components involved in these complex mechanisms. In classical studies, identification of salt tolerant cultivars and the genetic markers linked to salt tolerance and breeding approaches have been give emphasis for developing salt tolerance in rice. However, only limited success has been achieved in these approaches as salt tolerance is a complex process and is governed by multiple factors. Hence, for better understanding of salt tolerance mechanisms, a comprehensive approach involving physiological, biochemical and molecular studies is much warranted. Modern experimental and genetic resources have provided a momentum in this direction. Integrating the knowledge of classical and modern research in understanding of salt stress adaptive pathways will facilitate for designing effective strategies to combat salt stress. Hence, the present review focuses on the interdependency of classical and modern approaches and their integration for better understanding of salt stress tolerance mechanisms in rice.